(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The article analyzes the practical experience, theoretical and methodological backgrounds toformation of research competence of future software engineers. Also in this article we defined the content, structure, criteria and indicators of research competence of future software engineers and characterized levels of the formedness of research competence of futuresoftware engineers and explained main phases of its formation. In consideration of the specificity of formation of research competence of software engineers, job market requirements and social order much attention in article is paid to student participation in research projects of the Chair, particularly in international projects and projects commissioned by the Ministry of Education and Science of Ukraine. The important factor of effective formation of research competence of future software engineers is student’s work on chair of scientific schools, their training in IT companies and IT departments of higher education institutions and other educational establishments, including abroad. Also we pay attention to the need of group work of participants of the educational process that can beprovided with their participation in scientific problem groups, scientific schools, work on joint research projects. The conducted research confirms the effectiveness of implementation of the proposed model offormation of research competence of future software engineers.